Energy Partnerships: Us Involvement in Central Asian Resource Development - Author: Saidbek Mamasoliev (Zien Journals, 2024)
This research article aims to shed light on the changing role of the United States in Central Asian resource development and its implications for regional geopolitics and global energy security by exploring the complexities and dynamics of energy cooperation.
Keywords: Specific challenges; requires diversification; economic benefits and challenges for Central Asian nations